2020
DOI: 10.1177/0047287520962222
|View full text |Cite
|
Sign up to set email alerts
|

International Remittances as a Driver of Domestic Tourism Expenditure: Evidence from Mexico

Abstract: This article aims to empirically assess the impact of international remittances on domestic tourism expenditure (DTE) in Mexican households. Using Probit and Tobit regressions with instrumental variables and information from the 2016 National Household Income and Expenditure Survey, our findings show that international migrants’ remittances can improve DTE among Mexican households. Controlling for endogeneity of remittances, the results show a statistically significant and positive impact of international remi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…The channels in which migration and remittance can affect the economy documented in the empirical literature include short-run, long-run, and causal effects (Sevencan 2023;Chowdhury et al 2023). The existing research often focuses on specific regions or sectors, leaving a gap in understanding the short-and long-run implications for employment and tourism income (Ghani and Morgandi 2023;Noushad et al 2022;Mora-Rivera and García-Mora 2021).…”
Section: Gap Identified In the Empirical Literaturementioning
confidence: 99%
“…The channels in which migration and remittance can affect the economy documented in the empirical literature include short-run, long-run, and causal effects (Sevencan 2023;Chowdhury et al 2023). The existing research often focuses on specific regions or sectors, leaving a gap in understanding the short-and long-run implications for employment and tourism income (Ghani and Morgandi 2023;Noushad et al 2022;Mora-Rivera and García-Mora 2021).…”
Section: Gap Identified In the Empirical Literaturementioning
confidence: 99%
“…This section provides a review of the relevant literature analyzing the impact of IRM and PS on ITR. Although a few studies have analyzed the association between IRM and domestic tourism growth (Cerón and Mora, 2014;Mora-Rivera et al, 2019;Mora-Rivera and García-Mora, 2021), the empirical literature on the association between IRM and ITR remains inconclusive, especially in the context of South Asian countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past studies argue that there is a significant role of ITR in stimulating employment and economic growth (EG) in a country (Adedoyin et al, 2021;Briedenhann and Wickens, 2004;Mazzola et al, 2019;Paramati et al, 2017;Seetanah, 2011). Similarly, IRM is an important driver for the tourism sector, specifically for developing countries (Mora-Rivera and García-Mora, 2021). The Asian Development Bank (ADB) reported that South Asian countries received USD 139.8 billion from IRM in 2019 (Asian Development Bank, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation